Composição taxonômica e análise ecológica da ictiofauna da bacia hidrográfica do rio São João, RJ, Brasil - Bizerril, Carlos Roberto Silveira Fontenelle (1995)
Present informations about the taxonomic composition of the fish assemblages that inhabit the river São João Basin, RJ are presented, together with data concerning different levels of ecological relationships observed in the fish communities. Samples were taken monthly from January/1992 to December/1992 in 6 sample units, which were selected along the river channel and in 3 tributaries. Fishes were captured using manual seine-nets, cast-nets and sieves, with standardized catch efforts. Complementary qualitative data were obtained in random samples carried out in 9 additional sample units. Sample units were characterized considering the order, width, height and depth of the rivers, the presence\absence of riparian vegetation and the water speed, level and salinity. Pluviometric data were furnished by Companhia de Pesquisa de Recursos Minerais (CPRM). The constancy, relative abundance, feeding habits and the micro and meso-spatial distribution were analyzed for each species collected in quantitative samples. Community studies were made considering its qualitative and quantitative organization in taxonomic and trophic levels, applying various statistical methods of association. Smallest temporal changes in the environmental condtions were observed ln headwaters whereas severe alterations occurred in most of the low land environments and in the es1uarine reaches. 88 specles were sampled. Auto ecological data were obtained for 73 species. After analyzing together the spatial variation of constancy and relative abundance vatues, Microlepidogaster notatus, parotocinctus maculicauda, Otothyris kophophanes, Astyanax sp.2 e Astyanax giton were identified as the more euryecious taxa. A pattem that suggests the occurrence of spatial segregation by size was observed for Rhamdia sp., Plmeiodella lateristriga, Astyanax taeniatus. Hypostomus punctatus (with smaNest specimens occurring in tributaries whereas the biggest specimens inhabit the main channel), Astyanax sp.2, Astyanax giton, Bryconamencus tenuis e Characidium sp.3 (with largest specimens in the headwaters and smallest specimens in the lowlands). Thirteen trophic guilds were recognized. Most of the species presented generalist habits. A pattem of species richness increase was observed associated with reductions in the river slope. The same process was verified for the increase in the efflciency of the nutidlmensional use of spatlal resources and the ln trophic diversity of the fish assemblages. The contirun of increasing complexity of fish communities was interrupted due elevations in the overal dimensions of the rivers studied. Areas located in the upper sections presented highest faunistic stabillity, reflecting its rapid recuperation after changes produced by the rainfal regime. Pluviosity was identifled as the main ecologlcal factor that is causaly correlated with the community temporal changes.